Fiscal Decentralization and Economic Growth in South Africa: A South African Perspective - Mosikari, Teboho; Stungwa, Sanele (Acta Universitatis Danubius. Œconomica, 2023)
The objective of this study is to investigate the relationship between “fiscal decentralization and economic growth in South African. The study used an annual panel data for the period 2010-2019 across nine provinces. The study employed fixed effects model to investigate this relationship. To observe the order of integration of the variables, the study employed Levin, Lin, and Chu unit root test and Im, Pesaran, and Shin unit root test. The study found a positive relationship between economic growth and provincial government expenditure and provincial government revenue, fixed capital formation and capital stock in South Africa. Granger causality test further showed that there is a long run unidirectional causality running from provincial government expenditure to gross domestic product. The findings imply that South African government should fully adopt a fiscal decentralization policy to ensure an efficient provision of public goods and services to all the South African citizens.